Political socialization, worry about crime and antisocial behaviour: an analysis of age, period and cohort effects - Gray, Emily (The British journal of criminology, 2019)
Fear of crime occupies a substantial area of research and theorizing in criminology. Yet, it has not been examined within a longitudinal framework of political socialization. Using insights from generational modelling, we explore how political cohorts influence the fear of crime and perceptions of antisocial behaviour. This ‘age, period and cohort’ (APC) approach recognizes the distinct temporal processes of (1) individual ageing, (2) current contexts and (3) generational membership and is crucial to understanding the origins and shape of social change. We employ repeated cross-sectional data from the British Crime Survey in an APC analysis to explore how worry about crime and perceptions of antisocial behaviour were impacted by the sociopolitical environment in which respondents spent their ‘formative years’. Our results underline the theoretical significance of political socialization and the methodological consequence of longitudinal analyses when exploring public perceptions of crime. We find that political socialization can have a distinctive and enduring impression on public perceptions of crime from childhood into middle age.